Implementasi Program Kemitraan Dosen LPTK dan Guru di Sekolah dalam Merancang Pembelajaran Biologi berbasis LSLC (Lesson Study for Learning Community) di SMA Negeri 2 Limboto Kabupaten Gorontalo - Febriyanti, Febriyanti; Kandowangko, Novri Youla; Syafar, Sitti Zaenab; Husain, Holiyana; Rahman, Iyam; Ui, Maryam; Dali, Ira K. (Universitas Negeri Gorontalo, 2024)
There are numerous complex issues that can affect the quality of education in Indonesia. One of them is the low quality of learning and the perceived monotony. In the face of these challenges, teachers and lecturers, as agents of change, must continue to innovate. This writing is based on the partnership program between lecturers from Teacher Training and Education College (LPTK) and teachers from State Senior High School 2 Limboto, involving four biology teachers, the school principal, and one lecturer. The program aims to create interactive and effective biology learning for students. The proposed solution from this program is the implementation of Lesson Study for Learning Community (LSLC), consisting of three stages: Planning, implementation, and reflection, as a form of collaborative effort between lecturers and teachers in designing biology lessons. LSLC activities are conducted in three cycles with three Open Classes. Based on the completed stages, it can be concluded that the collaboration between lecturers and teachers through LSLC activities is highly beneficial and has an extraordinary impact on improving the quality of education. The collaboration between lecturers and teachers in each stage of LSLC activities demonstrates a tangible commitment to the education sector. Therefore, it is expected that a continuous collaboration with universities as school partners can be established.